Fractal Structure of Seismic Signals of 2015 Gorkha-Kodari Earthquakes: A Box Counting Method - Tiwari , Ram Krishna; Paudyal, Harihar (BMC Journal of Scientific Research, 2022)
Fractal dimension analysis is a computational image processing technique that allows assessing the degree of complexity in patterns. In seismology, fractal dimensions can be used to describe fractured surfaces quantitatively. The larger the fractal dimension the more rugged is the surface, the more irregular is the line, and the more complex is the pore space. For the present investigation the seismic wave signal of 40 earthquakes including one foreshock, main shock and 38 aftershocks (mb ≥ 5.0) of 2015 Gorkha-Kodari earthquakes from 2015/4/21 to 2016/11/27 were considered. The seismograms were retrieved from the archived waveform data of Incorporated Research Institutions of Seismology (IRIS). The fractal dimension (D) was evaluated by the Python program for box counting. It is found that the fractal dimensions of the seismic wave signal during the active seismic period do not show sudden variation and they are almost identical. The maximum value was noticed to be 1.99±0.006 and the minimum value to be 1.95±0.007. The estimated fractal dimension is greater or equal to 1.95 with an average value of 1.98 which signify the presence of high grade of fractality in seismic wave time series. This suggests that the fractal characteristics of the seismic wave signal of 2015 central Himalayan earthquakes occurrence behavior is nonlinear and coplanar.